Cubic Mesoporous Silica (SBA‐16) Prepared Using Butanol as the Co‐Surfactant: A General Matrix for the Preparation of FeCo‐SiO2 Nanocomposites. Issue 4 (19th March 2013) - Carta, Daniela; Bullita, Salvatore; Casula, Maria F.; Casu, Alberto; Falqui, Andrea; Corrias, Anna
Abstract A mesoporous ordered cubic Im3m silica (SBA‐16) characterized by a three dimensional cage‐like structure of pores was used as a host matrix for the preparation of a series of FeCo‐SiO2 nanocomposites with different alloy loading and composition by the wet impregnation method. The mesoporous structure of the SBA‐16‐type support, prepared according to a versatile sol‐gel templated synthetic method, which makes use of n‐butanol as a co‐surfactant, is stable during the treatments necessary to obtain the final nanocomposites, as pointed out by low‐angle X‐Ray diffraction, transmission electron microscopy, and N2 physisorption at 77 K. Wide‐angle X‐ray diffraction shows that upon reduction at 800 °C, FeCo nanocrystals (6–7 nm) with the typical bcc structure are formed and energy‐dispersive X‐ray spectroscopy analysis, performed by scanning transmission electron microscopy on one of the samples, shows that the Fe/Co atomic ratio in the alloy nanoparticles is very close to the expected value of two. Electron tomography was used for the first time to gain evidence on the highly interconnected mesoporous structure of SBA‐16 and the arrangement of the nanoparticles within the matrix. It was found that spherical alloy nanocrystals with narrow size distribution are homogeneously distributed throughout the mesoporous matrix and that the resulting FeCo‐SiO2 nanocomposite material displays superparamagnetic behavior with high strength dipolar interactions, as expected for particles with a large magnetic moment.